Post-Newtonian hydrodynamics theory and applications - Kremer, Gilberto Medeiros (Cambridge Scholars Publishing, 2022)
This book introduces and develops post-Newtonian kinetic and phenomenological theories in a self-contained manner. The starting point for phenomenological theory is Einstein's field equations from which the first and second post-Newtonian approximations are derived. Within phenomenological theory, Eulerian hydrodynamic equations are obtained and the conservation laws are derived. The kinetic counterpart of the theory is developed within the framework of Boltzmann equation, where the post-Newtonian equilibrium distribution function and the hydrodynamic equations are determined. Some astrophysic.